Counter-narcotics policy in Iraq after 2003 - Samer Nahed Khader Hassan Khadouri (Tikrit Journal For Political Science, 2025)
One of the most important goals of public policies taken by countries is to reduce negative phenomena that cause disruption in human behavior, resulting in extensive damage in various sectors of the State's political, security, economic and social life, This breach is caused by a number of reasons, The most important of which is the phenomenon of drug spread among community members, which is based on the deprivation of one's mental, health and financial abilities, Therefore this phenomenon has been and continues to receive significant attention from States to reduce it in general, And Iraq’s policies after 2003 in particular, Which sought, through its various legislative, executive, institutional and judicial mechanisms, to combat the negative effects resulting from it, Despite all the attempts made by the Iraqi state after the process of changing the political system to combat the phenomenon of drug spread, However, it faced major challenges that has stood against those policies, Which we will discuss in detail in the course of the research.